2016
DOI: 10.5902/2179460x24219
|View full text |Cite
|
Sign up to set email alerts
|

Vegetais Cultivados Em Quintais Rurais Piauienses Com Indicação Anticâncer: Uma Busca Pelo Conhecimento Tradicional

Abstract: Resumo Objetivou-se neste estudo, identificar as plantas medicinais com indicação anticâncer cultivadas em quintais pelos moradores da comunidade rural de Aroeiras

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…A few drops of the latex (a maximum of three) in a liter of water is indicated for the treatment of cancer. 27 Chamomile (10) Matricaria recutita L. Antispasmodic, anxiolytic, and mild sedative.…”
Section: Rosemary (6)mentioning
confidence: 99%
“…A few drops of the latex (a maximum of three) in a liter of water is indicated for the treatment of cancer. 27 Chamomile (10) Matricaria recutita L. Antispasmodic, anxiolytic, and mild sedative.…”
Section: Rosemary (6)mentioning
confidence: 99%
“…Schum., commonly known as Vinca rosea. Taxus brevifolia, a plant from which taxol is extracted, demonstrated high antitumor activity in the treatment of breast, ovarian, and lung cancers (Abreu et al, 2017). Silva et al (2012), Santos et al (2012), Povh &Oberlies et al (1997), reported that the extract of soursop (Annona muricate) leaves exhibited cancer-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…La necesidad de ampliar el uso de productos naturales para tratar esta enfermedad, abre las puertas a la búsqueda de actividad biológica de plantas que son usadas popularmente por presentar algún efecto con la enfermedad, como es el caso de la guanábana (Annona muricata), de la cual se han extraído metabolitos secundarios (acetogeninas) que presentan in vitro mayor toxicidad en líneas celulares cancerígenas comparadas con líneas celulares normales, y se concluyó, que las acetogeninas comprenden una fuente potencial para el desarrollo de medicamentos contra el cáncer 18 . Además, uno de los compuestos que se encuentran en la eficacia como agente anticancerígeno en el cáncer cervical y de la nasofaringe es la acetogenina, un compuesto policétido que es abundante en las hojas de guanábana 19,20,21 .…”
Section: Metodologíaunclassified